2010
DOI: 10.1111/j.1460-9568.2010.07150.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification of extracellularly recorded neurons by their discharge patterns and their correlates with intracellularly identified neuronal types in the frontal cortex of behaving monkeys

Abstract: Neurons in the cerebral cortex are not homogeneous. However, neuronal types have been ignored in most previous work studying neuronal processes in behaving monkeys. We propose a new method to identify neuronal types in extracellular recording studies of behaving monkeys. We classified neurons as either bursting or non-bursting, and then classified the bursting neurons into three types: (i) neurons displaying a burst of many spikes (maximum number of spikes within a burst; NSB max > or = 8) at a high discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 29 publications
8
39
0
Order By: Relevance
“…According to a previous study (Katai et al, 2010), we classified each of the SR neurons into two cell types, a putative regular spiking (pRS) neuron or a putative burst spiking (pBS) neuron, on the basis of interspike intervals (ISI). If the ISIs smaller than 5 msec accounted for less than 5% of all the ISIs recorded from the neuron, the neuron was classified as a pRS neuron.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study (Katai et al, 2010), we classified each of the SR neurons into two cell types, a putative regular spiking (pRS) neuron or a putative burst spiking (pBS) neuron, on the basis of interspike intervals (ISI). If the ISIs smaller than 5 msec accounted for less than 5% of all the ISIs recorded from the neuron, the neuron was classified as a pRS neuron.…”
Section: Discussionmentioning
confidence: 99%
“…These should be distinguished from narrow spiking neurons that lack burst firing, which are instead likely to correspond to fast-spiking interneurons. One recent study (Katai et al, 2010) has used spiking statistics to distinguish among four different cell classes in the frontal cortex of the behaving primate. Their study identified these with classes previously defined in slice (intrinsically bursting (IB), regular spiking (RS), fast spiking (FS), and fast rhythmic bursting (FRB)).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies in the awake primate that have examined spiking statistics in more detail have revealed a diversity of firing patterns across neocortical regions (Maimon and Assad, 2009) as well as across neurons recorded within individual cortical areas (Bair et al, 1994; Friedman-Hill et al, 2000; Compte et al, 2003; Joelving et al, 2007; Katai et al, 2010). Indeed, many intracellular recording studies have used discharge patterns such as bursting to distinguish among different neocortical neuronal classes (McCormick et al, 1985; Nowak et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Spike shape and timing were identified as key physiological features, notably firing rate, fast after-hyperpolarization depth of the first spike, as well as half-height width and latency from stimulus of the second spike. Other similar studies reported analogous distinctive electrophysiological parameters, namely rise, duration, and decay of the first two spikes, plus firing rate and spike duration at 10 Hz [21,58]. …”
Section: Advances In Automatic Neuronal Classificationmentioning
confidence: 69%